Meta Analysis: Factors Affecting Alcohol Consumption in Adolescents - Ihsan Hanif; Ardiana Mardiah; Rachmawaddah Yolanda; Bhisma Murti; Siti Mar'atul Munawaroh (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Since alcohol is obtained easily, so it tends to be widely abused. The factors that cause a teenager to consume alcohol are individual factors/individual personality, and environmental factors. This study aims to estimate the factors that affect alcohol consumption in adolescents. Subjects and Method: This study used systematic review and meta-analysis using PICO. Population: adolescents. Interventions: drinking parents, drinking friends, smoking. Comparison: non-drinking parents, non-drinking friends, non-smoking. Result: alcohol consumption. The articles used in this study were derived from 2 databases, namely Google Scholar and Science Direct. The article's keywords were